Analiza strategiczna opcji rzeczywistych. Model Luehrmana - Kempiński, Marek (Strategic Analysis of Real Options. Luehrman's Model, 2008)
This article deals with a problem of putting real options analysis into practice, especially in case of small and medium-sized companies. The central issue is a presentation of Luehrman's model, is an attempt to simplify Black-Scholes model, widely used to value real options. The added advantage of the approach is the possibility of graphic presentation of relations between particular real options. Luehrman's model can also be used to analyze a company's strategy, presented as a portfolio of real options.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 263-271